Paper 28: Early Versus Standard Return to Sport Following ACL Reconstruction. Impact on Volume of Play and Career Logevity in 180 Professional European Soccer Players. Issue 7 (30th July 2022) - Provencher, Matthew; Mariani, Pier; Haber, Daniel; Peebles, Annalise; Arner, Justin; Midtgaard, Kaare; Peebles, Liam; Kures, Alexander; Guglielmo, Torre; Battaglia, Michael
Objectives: To retrospectively evaluate the impact of early(<6 months) vs standard(>6months) return to play(RTP) on the rate of failure, volume of play, and career longevity following ACL reconstruction in a cohort of professional European soccer players. It was hypothesized that athletes returning to professional competition earlier than 6 month after ACL reconstruction would not have an increased risk of failure, volume of play, and a shorter professional career. Methods: Professional soccer players treated for anterior cruciate ligament tear by a single surgeon were included in this retrospective study. The study was approved by the institutional review board. The inclusion criteria were that the patient was a (1) male, (2) professional soccer player with an (3) injury of the anterior cruciate ligament. Exclusion criteria were revision ACL, extra-articular ligamentous reconstruction, and previous contralateral ACL reconstruction. A total of 178 players who were all in the first or second division of their league met criteria for the study over a ten year period. Time from intervention to return to the first official game was recorded in days. Information if the patient was able to return to the same season was recorded, as well as the number of games and total and average minutes played in the return season. Number of seasons played after injury and if the player was active at the time of data collection (September 2019) was also recorded. If the player was still active, the player's current club was recorded. Results: 90-early RTP and 88 standard RTP players were identified. Players in the early RTP group returned to professional level soccer at a mean of 4.76 months, which was significantly sooner than players in the standard RTP group who returned at a mean of 9.21 months (p < 0.01) following ACLR. A significantly greater number of players in the early RTP group returned during the same season of intervention (n = 56/92, 60.9%) than in the standard RTP group (n = 18/88, 20.5%) (p < 0.01). Players in the early RTP group competed in an average of 11.5 games during their return season while those in the standard RTP group competed in an average of 12.9 games (p > 0.05). The early RTP group played, on average, a total of 759.2 minutes and 56.5 minutes/game in their return season, while the standard RTP group played an average of 812.8 total minutes and 50.0 minutes/game in their return season (p > 0.05). Players in the early RTP group had significantly longer careers following ACLR, averaging 5.62 seasons, compared to those in the standard RTP group who competed in an average of 4.75 seasons after surgical intervention (p < 0.01). The early RTP group had 4 failures while the late RTP group had 1 failure failure. Conclusions: Professional European soccer players who return to play earlier than 6 months after ACL reconstruction returned more frequently during the same season, played the same number of games and minutes during their return season, had longer careers, but had more ACL graft failures when compared with those who returned greater than 6 months after surgery. Professional European soccer players who returned early after ACL reconstruction (<6 months) did not appear to have poorer outcomes, however caution should be taken before extrapolating this to the general population as these athletes have exceptional resources, fitness, and athletic capacity. Decision on return to play ultimately lies with the patient/athlete as prolonged RTP has significant financial and career consequences.